Society and Economy: Frameworks and Principles: A Book Review - Goyal, Sanjeev (Journal of Economic Literature, 2019)
Mark Granovetter has written a deep and wide-ranging book on economy and society entitled Society and Economy: Frameworks and Principles. Economists, in particular, will find his discussion on the role of social networks in understanding the problem of aggregation—from micro foundations to large-scale institutional phenomena—especially relevant. And they will find much to ponder over the ways in which overlapping structures—of networks and institutions—shape human behavior and determine aggregate economic outcomes. The high-level and parsimonious style of this book is distinctive and sets it apart from much of contemporary social science. This style and the apparent unwillingness to engage closely with research developments over the past two decades may, however, mean that the book will have limited influence on ongoing and future research. (JEL D02, D90, Z13)